Pengaruh Tingkat Pengetahuan dan Tingkat Kepatuhan pada Pasien Tuberkulosis di Puskesmas PB Selayang II Kota Medan - Arbita Huri; Erida Novriani; Razoki, Razoki (CV. ITTC INDONESIA, 2025)
Background: Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis.Mycobacterium species, including: M. tuberculosis, M. africanum, M. Bovis, M. Leprae are Acid Resistant Bacteria (BTA). in Indonesia TB reached 842,000 cases in 2018 with a mortality of 107,000 cases. With this data, Indonesia is the country with the third highest TB disease in the world. Objective: To determine the effect of Knowledge Level and Compliance Level on TB patients at PB Selayang II health center in Medan City. Methods: the study used quantitative, cross sectional research design approach. The sample in this study were 36 respondents who were willing to use purposive sampling technique, and data collection using a questionnaire. Research Results: the results of data processing on 21 respondents had a sufficient level of knowledge of 58.3% and as many as 27 respondents had a moderate level of compliance of 75.0%. In the Pearson Chi Square results p = 0.003 The results of the correlation analysis with the Chi-Square test can be interpreted that there is an influence between the level of knowledge and the level of compliance with taking medication for Tuberculosis Patients at the PB Selayang II Health Center, Medan City.